2020
DOI: 10.3390/plants9070913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dark Septate Endophytes Strain A024 on Damping-off Biocontrol, Plant Growth and the Rhizosphere Soil Enviroment of Pinus sylvestris var. mongolica Annual Seedlings

Abstract: Dark septate endophytes (DSEs) exert a vital role in promoting plant growth, improving mineral absorption, biological disease control, and enhancing plant stress resistance. The effects of dark septate endophyte strain, Phialocephala bamuru A024 on damping-off biocontrol, plant development, nutrients within the rhizosphere soil, as well as bacterial communities in the annual seedlings of P. sylvestris var. Mongolica were studied. According to our findings, following P. bamuru A024 inoculation, the damping-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 50 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The distribution range of DSEs includes more than 600 species of plants from 114 families and 320 genera (Liu et al 2009). DSEs play a vital role in promoting plant growth, improving mineral absorption and biological disease control, and enhancing plant stress resistance (Deng et al 2020). By secreting organic acids or enzymes, DSEs decompose the organic substances in the soil that cannot be directly absorbed and utilized by plants (such as nitrogen, phosphorus and other substances) into forms that can be absorbed and utilized by plants to improve the utilization e ciency of plants for organic substances in the soil and promote the growth and development of plants (Newsham 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution range of DSEs includes more than 600 species of plants from 114 families and 320 genera (Liu et al 2009). DSEs play a vital role in promoting plant growth, improving mineral absorption and biological disease control, and enhancing plant stress resistance (Deng et al 2020). By secreting organic acids or enzymes, DSEs decompose the organic substances in the soil that cannot be directly absorbed and utilized by plants (such as nitrogen, phosphorus and other substances) into forms that can be absorbed and utilized by plants to improve the utilization e ciency of plants for organic substances in the soil and promote the growth and development of plants (Newsham 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the increase in the proline content of Ac-inoculated A. ordosica was significantly higher than that of the control under drought conditions. Previous studies have also found that inoculation of fungi can increase the accumulation of osmotic adjustment substances and reduce the osmotic potential of host cells, so as to resist dehydration injury caused by stress [ 102 , 103 , 104 ]. This is in accordance with a recent study by He et al [ 65 ], who found that A. vagum can enhance the drought tolerance of the host plant Astragalus mongholicus .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the important role of endophytic fungi in enhancing plant growth and tolerance under abiotic stress. DSE play a role in growth promotion and nutrient uptake in plants as they are rich in plant cell wall‐degrading enzymes, which can degrade complex organic substrates (Knapp et al 2018; Deng et al 2020). The colonization of host plants by DSE assists plants in the uptake of nutrients in nutrient‐deficient soils and increases the tolerance of plants in stressful environments (Vergara et al, 2017).…”
Section: Discussionmentioning
confidence: 99%